Microstructural Evolution and Service Performance of Cold-drawn Pure Aluminum Conductor Wires. Issue 9 (September 2017) - Luo, X.M.; Song, Z.M.; Li, M.L.; Wang, Q.; Zhang, G.P.
Abstract : Microstructures and service performance (mechanical and electrical properties) of the commercially pure Al conductor wires subjected to different cold drawing strains were investigated. The results show that the microstructures of the cold-drawn Al wires along the radial direction were inhomogeneous, i.e. the texture in the center region was strong <111> and weak <001> components, while that in the surface region shifted from the initial cubic texture to a <112> component and finally developed into a strong <111> component. The volume fraction of the high angle grain boundaries in the surface region was higher than that in the center region. The cold-drawing process greatly enhanced the yield strength of the pure Al wires while retained the acceptable electrical resistivity. The strengthening mechanism and the variation of electrical conductivity of the cold-drawn Al wires are discussed through correlating with microstructure evolution.